Pengaruh Ukuran Perusahaan, Leverage, Dan Likuiditas Terhadap Pengungkapan Corporate Social Responsibility Dengan Profitabilitas Sebagai Variabel Moderasi - Fitri Aulia Arif; Andi Wawo (Universitas Islam Negeri Alauddin Makassar, 2016)
This study aims to provide empirical evidence that firm size, leverage and liquidity affect the disclosure of corporate social responsibility and profitability in moderating the relationship of the three dependent variables.This research is quantitative. Subject of this research is manufacturing companies listed in Indonesia Stock Exchange 2011-2013. Elections were conducted with a purposive sampling method, in order to obtain 34 companies that meet the criteria with three years of observation. The data used is secondary data derived from the financial statements and annual reports, while data analysis technique used is descriptive statistical analysis and regression analysis.Based on the results of hypothesis testing multiple regression showed that the variables of firm size, leverage and liquidity significant positive effect on the disclosure of corporate social responsibility, and profitability moderate the relationship of liquidity and leverage on the disclosure of corporate social responsibility, but not moderate sized companies on disclosure of corporate social responsibility.